1983
DOI: 10.1002/jcu.1870110607
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic prenatal diagnosis of fetus in fetu

Abstract: "Fetus in fetu" is a rare pathologic feature consisting of a parasitic twin included within the body of the other twin. ' As reported by Lee,2 only 13 cases have been described since 1900. Nearly all cases were diagnosed during surgery within the first year ofWe report a case detected during a prenatal ultrasound examination as a fetal abdominal mass. CASE REPORTS.L., a 20-year-old woman in her first pregnancy, was referred to our Department at the 35th week for a suspected fetal anomaly detected elsewhere b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Although the diagnosis of an FIF has traditionally been made in infancy or childhood, there are an increasing number of diagnoses being made prenatally on the basis of sonography. 1,[4][5][6][7][8][9][10][11][12][13][14] This report describes the prenatal diagnosis of an FIF with an extraordinarily high degree of differentiation using two-dimensional (2D) and three-dimensional (3D) sonographic imaging.Abbreviations FIF, fetus in fetu; 3D, three-dimensional; 2D, two-dimensional…”
mentioning
confidence: 99%
“…Although the diagnosis of an FIF has traditionally been made in infancy or childhood, there are an increasing number of diagnoses being made prenatally on the basis of sonography. 1,[4][5][6][7][8][9][10][11][12][13][14] This report describes the prenatal diagnosis of an FIF with an extraordinarily high degree of differentiation using two-dimensional (2D) and three-dimensional (3D) sonographic imaging.Abbreviations FIF, fetus in fetu; 3D, three-dimensional; 2D, two-dimensional…”
mentioning
confidence: 99%
“…(9) In today's technologically advanced world, prenatal diagnosis is on the rise. Diagnosis with US was first reported by Nicolini et al (10) CONCLUSION Foetus-in-foetu (FIF) is a rarely diagnosed condition. FIF could be considered as a rare differential of teratoma in an infant or young child presenting with progressively increasing abdominal swelling and vomiting.…”
Section: Discussionmentioning
confidence: 97%
“…In 1983, Nicolini et al [8] reported a case of fetus-in-fetu diagnosed after birth in which a cystic tumor in a fetus that included a solid calcified component surrounded by fluid turned out to be fetus-in-fetu. In 1997, Chen et al [9] reported a case prenatally diagnosed as fetus-in-fetu by identification of a calcified vertebral column and long bones within a fetal intra-abdominal cystic mass.…”
Section: Discussionmentioning
confidence: 99%